Sexual health among young bisexual women: a qualitative, community-based study. Issue 1 (3rd April 2017) - Flanders, Corey E.; Ross, Lori E.; Dobinson, Cheryl; Logie, Carmen H.
ABSTRACT: Young bisexual women experience health disparities related to sexual health, yet there is comparatively little research that addresses which specific factors drive these disparities. The current study investigates young bisexual women's perspective of their sexual health in order to address this gap. We conducted a community-based qualitative study in Canada, which included four two-hour focus group sessions with 35 bisexual women (broadly defined as bisexual and other nonmonosexual people who self-identify as women, cisgender and transgender inclusive). Focus group sessions were transcribed verbatim and analysed from a grounded theory approach. Young bisexual women perceive various forms of stigma, most notably binegativity and monosexism, as negatively impacting their sexual health. This stigma creates barriers at the institutional and interpersonal level to maintaining positive sexual health. Young bisexual women relate substantial negative health consequences to stigma, including a dearth of applicable health resources and risk of sexual violence. Participants suggest a number of ways in which their health could be supported.